The Significance of Adaptation Interventions as a Tool to Protect the World Heritage Properties from the Negative Impacts of Climate Change. - Kola O. Odeku (African Journal of Hospitality, Tourism and Leisure, 2018)
There are numerous natural and cultural world tourism heritage sites spread across the entire landscape of the world, which are of outstanding universal value. These sites attract tourists from all over the world for different reasons such as for sightseeing, heritage and archaeological interest, education and research. The concern is that global warming and climate change are posing huge threats to most of these sites and properties by altering, deteriorating and ravaging them. In order to address these problems and find sustainable solutions, this article identifies a climate change adaptation strategy as the potential intervention that can be utilised to enable these sites and properties to cope with the prevailing unusual climatic conditions in order to sustainably protect and preserve them for the present and future generations to enjoy.